Using Cost Observation to Regulate Firms - Laffont, Jean-Jacques; Tirole, Jean (Journal of Political Economy, 1986)
The paper emphasizes the use of accounting data in regulatory or procurement contracts when the supplier (1) has superior information about the cost of the project and (2) invests in cost reduction. The main result states that, under risk neutrality, the supplier announces an expected cost and is given an incentive contract linear in cost overruns. This (optimal) contract moves toward a fixed-price contract as the announced cost decreases. An investment choice is then introduced and the use of a rate-of-return regulation is studied.